2017
DOI: 10.1038/ncomms14122
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear stress activates YAP1 to promote cancer cell motility

Abstract: Mechanical stress is pervasive in egress routes of malignancy, yet the intrinsic effects of force on tumour cells remain poorly understood. Here, we demonstrate that frictional force characteristic of flow in the lymphatics stimulates YAP1 to drive cancer cell migration; whereas intensities of fluid wall shear stress (WSS) typical of venous or arterial flow inhibit taxis. YAP1, but not TAZ, is strictly required for WSS-enhanced cell movement, as blockade of YAP1, TEAD1-4 or the YAP1–TEAD interaction reduces ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
223
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(236 citation statements)
references
References 70 publications
6
223
1
Order By: Relevance
“…In cancer associated fibroblasts (CAFs), YAP activation has been shown to enhance and maintain a positive feedback loop with actomyosin contractility [4]. Similarly, fluid shear-dependent YAP activation has been shown to enhance protrusions required for migration [33]. Second, cells are able to sense immediate matrix stiffness through adhesions, despite YAP depletion (results from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer associated fibroblasts (CAFs), YAP activation has been shown to enhance and maintain a positive feedback loop with actomyosin contractility [4]. Similarly, fluid shear-dependent YAP activation has been shown to enhance protrusions required for migration [33]. Second, cells are able to sense immediate matrix stiffness through adhesions, despite YAP depletion (results from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently,m icrofluidic culture technology in conjunction with tissue engineering has been developedf or studies in cell biology because many biological questions must be answered on the microscale. [89,90] To examine the effect of membrane fluidity on the modulation of mechanochemicals ignal transduction, a lipid-targeting molecular rotor,9 -(2-carboxy-farnesylester-2-cyanovinyl)-julolidine (FCVJ), was used to probe for lipid viscosity. Mechanochemical transductionoccurs when membrane-associated signaling proteins are activated by the increased intramolecular mobility.Anumber of studies have suggested the role of heterotrimeric Gp roteins in the mediation of cellular responses to fluid shear stress.M icroscopic imaging of FL intensity and lifetime of FCVJ in lipid layers allowed relatively fast and simple measurement, toe xamine the hydrodynamic shear stress can stimulate cellular mechanochemical transductionb y increasing membrane fluiditya nd activating heterotrimeric G proteins.…”
Section: Microfluidicapplicationsmentioning
confidence: 99%
“…In two recent studies, low fluid shear stress was found to induce tumor cell metastasis in cancer (Huang et al, 2018) and in at least one study, tumor metastasis was driven by the stimulation of the YAP1 gene, in the PRAD cancer (Lee et al, 2017). Thus supporting PoTRA's conclusion that the fluid shear stress and atherosclerosis pathway is the most dysregulated pathway for the TCGA PRAD project ( Table 5).…”
Section: Most Highly Ranked Dysregulated Pathwaysmentioning
confidence: 53%